Understanding Failure analysis using harmonic analysis and empirical mode decomposition techniques. (September 2022) - Nandi, Sounak; Subba Reddy, B.
Highlights: Failure Studies of FRP rods used in Composite Insulators. Using Empirical Mode Decomposition for Failure Detection. Minimal Data Input for remote monitoring of FRP failure using leakage current. Abstract: The investigation pertains to the failure analysis of Fibre Reinforced Plastic rods used in overhead transmission line insulators using appropriate data acquisition and analysis. The leakage current data, over an experimental period is captured and time–frequency analysis is implemented for determining the in-service condition of the overhead transmission insulators. It is observed from the investigation that the signal displays various events like dry-band arcing, partial surface arcs and triple-point discharges at the electrodes. The study presents a simple time–frequency analysis used for presenting the phenomena, an algorithm is developed for the harmonic analysis, also Empirical Mode Decomposition is conducted to reinforce the analysis. The main focus of the study is to estimate the early failures with minimal time and with available data.